The last resort - Kelly, Erin Entrada (Last resort, 2025)
Twelve-year-old Lila has two goals for the summer: 1. Win back the friends who ditched her for being "too dramatic" 2. Stop being so dramatic But then Lila's estranged Grandpa Clem dies, throwing a wrench in her plans. Now she'll have to spend the summer in Ohio while her parents decide what to do with Grandpa Clem's creepy Victorian Inn. It's supremely unfair. How can she show off the "new and improved" Lila from so far away? Even worse, strange things keep happening. En route to Ohio, the family gets into a scary car accident. No one's hurt, but the remainder of the trip is... odd. At every rest stop, Lila sees people in weird old-fashioned clothes. People no one else can see or hear... Lila convinces herself it's just her overactive imagination until the day of the funeral when she spots an old man sitting in her grandfather's favorite chair. She does a double take -- it's him, Grandpa Clem. He tells Lila that he didn't die of a heart attack: he was murdered. Possibly by someone who wants to control the inn. Because it's not a normal bed & breakfast: it's a portal between the land of the living and the realm of the dead. A hotel for ghosts passing onto the afterlife. With the help of her skeptical brother, Caleb, and their new ghost-obsessed neighbor, Teddy, Lila -- the girl who's vowed to be less dramatic -- must uncover her grandfather's killer AND stop the evil spirits desperate to make their way back into the human world.